Phase I Study of Muscadine Grape Extract for Patients With Advanced Cancer. (June 2021) - Bitting, Rhonda L.; Tooze, Janet A.; Isom, Scott; Petty, W. Jeffrey; Grant, Stefan C.; Desnoyers, Rodwige J.; Thomas, Alexandra; Thomas, Christopher Y.; Alistar, Angela T.; Golden, Shannon L.; Pleasant, Katherine; Chappell, Mark C.; et al.
Abstract : Objective: Preclinical studies with muscadine grape extract (MGE) show antitumor activity and decreased systemic inflammation. This phase I study (NCT02583269) assessed safety and tolerability of a proprietary MGE preparation in patients with advanced solid tumors. Methods: Patients with metastatic or unresectable cancers who were progressing on standard therapies were assigned to MGE in a standard 3+3 design. Five dose levels were tested (320 to 1600 mg total phenolics/d). Safety and maximum-tolerated dose were assessed after 4 weeks. Patients were evaluated for response at 8 weeks and continued on MGE if clinically stable. Secondary outcomes were response, survival, adherence, fatigue, and quality of life (QOL). Results: In total, 23 patients (lung, n=7; gastrointestinal, n=7; genitourinary, n=6; other, n=3) received MGE capsules by mouth twice daily. The cohort [median age 72 years, 48% Eastern Cooperative Oncology Group (ECOG) 2] was heavily pretreated. After 4 weeks on MGE, possibly attributable adverse events grade 2 or higher were fatigue (n=1), decreased lymphocyte count (n=1), and constipation (n=2), including 1 dose-limiting toxicity for grade 3 constipation. Maximum-tolerated dose was not reached. No partial responses were observed. Median time on therapy was 8 weeks, with 29% of patients treated beyond 16 weeks and a median overall survival of 7.2 months. QOL and fatigue levels were stable from baseline to 8 weeks. Higher MGE dose was correlated with improvement in self-reported physical well-being QOL at 8 weeks ( r =0.6; P =0.04). Conclusions: MGE is safe and well-tolerated in heavily pretreated and older cancer patients. The potential anticancer properties and the effects of MGE on physical well-being and QOL metrics will be evaluated in future studies. Abstract : Supplemental Digital Content is available in the text.